Implementation of Accountability and Transparency In The Allocation of School Operational Assistance Funds (BOS) During Covid-19. - Fatima, Nurul Asda; Haliah, Haliah; Nirwana, Nirwana (Amsir Management Journal, 2022)
UPT SD Negeri 191 Bubun Bia is one of the public schools that also received attention in the form of BOS funds from the government. The purpose of this study was to find out how to apply the principles of transparency and accountability in the management of BOS funds during the COVID-19 pandemic at UPT SD Negeri 191 Bubun Bia. This study uses qualitative methods with descriptive analysis and data collection techniques by means of observation, interviews, and documentation. The distribution of BOS Funds is based on the total number of students, totaling 104 students. The population in this study amounted to 218 people with a sample using purposive sampling of as many as 9 people. The results showed that the application of the principle of transparency at the UPT SD Negeri 191 Bubun Bia was transparent, as seen from the openness in the planning of preparing the RKAS. The benefits of this research are to provide mutual trust between various parties and the transparency of financial statements that can be accounted for